The First Tranche of Aid to Greece – Assumptions and Effects (Economic and Political Thought, 2012)
Greece is one of the Eurozone countries that have been severely strickenwith public debt crisis since 2009. Without the financial help from the EuropeanUnion and the International Monetary Fund, Greece would not be ableto repay its debts to the creditors. The condition for providing aid to thiscountry was that Greece commits itself to a macroeconomic program aimedat stabilizing public finance and regaining the capability of raising fundingresources on the financial markets on its own. The practice shows that as aresult of the implementation of the program the situation of Greece has notimproved at all but worsened. It turned out that it is necessary to restructurethe Greek public debt and this may lead to considerable losses for theinvestors. The possible results of such restructuring for Greece as well asthe Eurozone and other European Union countries, including Poland, arevery difficult to predict. The first tranche of the bailout program for Greeceproved to be ineffective in solving the problem of its public debt.